Panel Survey Estimation of the Impact of Urbanization in China: Does Level of Urbanization Affect Healthcare Expenditure, Utilization or Healthcare Seeking Behavior?. Issue 3 (4th May 2021) - Shi, Lu; Smit, Ellen; Luck, Jeff
Abstract: With its growing economy and changing society, China experienced a dramatic increase in urbanization during the past three decades. We explored the impacts of urbanization on healthcare utilization, healthcare expenditure and healthcare seeking behavior changes in China. Using a panel sample drawn from the China Health and Nutrition Survey, we estimated expenditures with a panel two-part model and a log transformation in the second part of the model. We estimated healthcare utilization and healthcare seeking behavior with generalized structural equation models and inpatient seeking behavior with a logit model. The sample contained 9, 052 respondents who were over 18 years old. We found that increased urbanization would lead to increased total treatment cost and out-of-pocket cost. We also found that urbanization changed general healthcare seeking behavior, including physician visits, but not inpatient seeking behavior. Lastly, not only urbanization level, but also insurance had significant impacts on healthcare expenditure and utilization and healthcare seeking behaviors. These observations provide support for addressing healthcare policy as a component of societal development.